2015
DOI: 10.1186/s13063-015-0972-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct improvement of quality of life in colorectal cancer patients using a tailored pathway with quality of life diagnosis and therapy (DIQOL): study protocol for a randomised controlled trial

Abstract: BackgroundMedical treatment in patient-centred care in oncology is broadly managed and regulated in terms of guideline development, cancer centres, and quality assurance by cancer registries. In contrast to this quality management cycle (PDCA), there are no equal standards for patient-reported outcomes like quality of life (QoL). Therefore, the Tumour Centre Regensburg e.V., a population-based regional cancer registry covering a population of more than 2.2 million people in the Upper Palatinate and Lower Bavar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…fatigue are the most frequently observed symptoms in patients receiving chemotherapy in South Korea (27), and all of these symptoms can significantly reduce the QOL of patients (28). Many clinical studies have demonstrated a reduction in the QLQ of colorectal cancer patients in western countries (29)(30)(31). In our study, all of these adverse effects and the reduction of QLQ-C30 scores were observed in patients receiving chemotherapy plus placebo.…”
Section: Discussionsupporting
confidence: 60%
“…fatigue are the most frequently observed symptoms in patients receiving chemotherapy in South Korea (27), and all of these symptoms can significantly reduce the QOL of patients (28). Many clinical studies have demonstrated a reduction in the QLQ of colorectal cancer patients in western countries (29)(30)(31). In our study, all of these adverse effects and the reduction of QLQ-C30 scores were observed in patients receiving chemotherapy plus placebo.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, patients with very ‘curable’ disease may want to explore treatment options with reduced chance of cure but minimal impact on health-related quality of life (HRQOL). 127 Current research continues to investigate treatments that minimise toxicity (SCOT and IDEA trials) 128 129 or amplify survival for patients undergoing established treatments (eg, ADD-ASPIRIN, CHALLENGE and FOxTROT trials). 130–132 …”
Section: Evidence Base For Research Gapss and Recommendationsmentioning
confidence: 99%
“…Half a year after the start of treatment, patients in the intervention arm reported better quality of life than patients in the control arm [28]. A recent RCT on patients with colorectal cancer confirmed this finding [29].…”
Section: Discussionmentioning
confidence: 89%